Molecular insights and concepts to engineer singlet fission energy conversion devices - Casillas, Ruben; Papadopoulos, Ilias; Ullrich, Tobias; Thiel, Dominik; Kunzmann, Andreas; Guldi, Dirk Michael (Energy and Environmental Science, 2020)
In thisReview, we showcase the fundamental processes of intermolecular and intramolecular singlet fission (SF). Furthermore we prioritize the information, which is relevant for the implementation of SF and SF-materials into solar energy conversion devices. We do this, firstly, by referring to the complexity of SF, and discussing key aspects of it; secondly, by mentioning the instrumental efforts, which assisted in unraveling SF in benchmark molecular building blocks such as tetracene, pentacene, and their corresponding dimers/oligomers; thirdly, by presenting a collection of SF-materials, as well as available photophysical and electrochemical data for energy conversion research. Among others, these include perylene-diimides (PDIs), diketopyrrolopyrroles (DPPs), carotenoids, conjugated polymers, and diradicaloids. This Review is rounded off by discussing pioneering contributions of SF in solar energy conversion schemes and highlighting recent developments in the field. Overall, a set of guidelines is given for new directions in SF, that is, the use of new tools to discover new SF-materials (i.e.spectroscopy, computation, machine-learning) and deposition processes (i.e.thin-films, DSSCs, OPVs) to couple SF-materials with the appropriate semiconductors.
CRIS-Team WoS Importer:2020-10-02